The Case of the Migrating Loop Recorder - Hasnie, Ali A. (JACC Case Rep, 2019)
The role of ambulatory electrocardiographic monitoring has changed considerably in recent years with the increased use of implantable loop recorders with their shrinking size. With an excellent safety profile from previous studies, their use is generally seen as a low-risk procedure. Despite this, unexpected complications can occur, including unexpected migration. (Level of Difficulty: Intermediate.)